A vision of re-distributed manufacturing for the UK’s consumer goods industry - Bessière, D.; Charnley, Fiona; Tiwari, Ashutosh; Moreno, Mariale (Taylor and Francis, 2019)
The linear production of consumer goods is characterised by mass manufacture, multinational enterprises and globally dispersed supply chains. Redistributed manufacture (RDM) is an emerging topic, which seeks to enable a transition of the current linear model of production and consumption, by taking advantage of new technologies. This paper aims to explore the challenges, opportunities and further research questions to set a vision of Redistributed manufacturing for the UK’s consumer goods industry. To set this vision, a literature survey was conducted followed by a qualitative enquiry where PESTLE aspects of RDM were analysed. This analysis was interpreted through a roadmap. As a result of this roadmap, four RDM characteristics (i.e. customisation, use of digital technologies, local production, and the development of new business models) were identified. These characteristics helped to set the future vision of RDM in the UK’s consumer goods sector
Keywords: Consumer Goods Industry; (Re) Distributed Manufacture; Customisation; Digital Technologies; Business Models; Local Production